Single Nucleotide Polymorphisms Associated with Alcohol-Induced Flushing Syndrome in Korean Population - Lee, Ji Hyun; Seo, Hee Jin; Cho, Sohee; Kim, Moon-Young; Lee, Soong Deok (Korean Journal of Legal Medicine, 2019)
Alcohol-induced flushing syndrome is one of the alcohol hypersensitivity reactions commonly found among Asian population. This study was designed to find markers that can predict this particular propensity among Korean population and to assess the applicability of this finding to build a prediction model as forensic DNA phenotyping tool to operate in practical forensic cases. Five hundred seventy unrelated Koreans were genotyped using microfluidic technology with 24 possible candidate single nucleotide polymorphism (SNP) markers. Of the 24 candidate SNPs, four markers, rs671, rs2074356, rs4646776, and rs10849915, on chromosome 12 showed statistically significant association with P-values ranging from 1.39×10-14 to 0.004988 among our subjects. All four markers show relatively high specificity values, ranging from 0.804651 to 0.972093, presenting their capabilities as differential SNPs that can distinguish a person with or without alcohol-induced flushing syndrome. Maneuvering these candidate SNPs as well as finding additional potential markers through future studies will help building an appropriate prediction model for Koreans that can be used as supplementary tool for individual identification. KCI Citation Count: 0